The Unofficial Guide to Medical and Surgical Emergencies - Manoharan, Varshini; Muralidharan, Vijaytha (Philadelphia, PA : Elsevier, 2024)
The Unofficial Guide Medical and Surgical Emergencies offers a collection of common clinical emergency scenarios. It walks you through the practical steps of the decision-making process, from taking a referral through to making a management plan and prescribing - all designed to ensure safe and best practice.
Includes bibliographical references and index.
Keywords: Emergency medicine